Extracting business value from semi-structured data - Thompson, Cindi; Steier, David; Safari eBooks; O'Reilly Strata making data work conference ([S.l.] : O'Reilly Media, 2011)
"Much useful business data is in "semi-structured" form: government filings, insurance claims, customer comment forms, etc. Although most search tools don't take advantage of it, knowing a little structure goes a long way. This talk will show how semi-structured data can be interpreted, summarized, and applied to produce business value in several real-life examples"--Resource description page.
Presenter, Cindi Thompson (for David Steier).
Recorded at the O'Reilly strata making data work conference, held at Santa Clara, Calif., Feb. 1-3, 2011.
Keywords: Database management; Database design; Electronic data processing; Electronic books